2021
DOI: 10.1111/risa.13668
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Managing Poliovirus Risks: We are Where we are…

Abstract: This introduction for the third special issue on modeling poliovirus risks provides context for the current status of global polio eradication efforts and gives an overview of the individual papers included in the issue. Although risk analysis continues to support the Global Polio Eradication Initiative (GPEI), efforts to finish the job remained off track at the beginning of 2020 and prior to the COVID‐19 pandemic, as discussed in the special issue. The disruptions associated with COVID‐19 occurring now will i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Smallpox was eradicated by 1980 (Freund, 2020 ; Tognotti, 2010 ), and while the campaign to eradicate polio has been challenged by residual reservoirs of wild polio virus together with recent difficulties and lapses in vaccination efforts (Tomori, 2018 ), the global effort has made tremendous progress (Matlin et al., 2017 ): the Global Polio Eradication Initiative (GPEI) has certified global eradication of wild poliovirus serotypes 2 and 3, and serotype 1 wild poliovirus transmission now remains only in Afghanistan and Pakistan. (Chumakov et al., 2021 ; Thompson, 2021 ; Thompson & Kalkowska, 2020 ; Thompson & Kalkowska, 2021 ; WHO, 2021b ). With these advances, immunization has been lauded as one of the biggest public health successes, saving 2–3 million lives a year without counting the contribution of COVID‐19 vaccines (United Nations Children's Fund [UNICEF], 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Smallpox was eradicated by 1980 (Freund, 2020 ; Tognotti, 2010 ), and while the campaign to eradicate polio has been challenged by residual reservoirs of wild polio virus together with recent difficulties and lapses in vaccination efforts (Tomori, 2018 ), the global effort has made tremendous progress (Matlin et al., 2017 ): the Global Polio Eradication Initiative (GPEI) has certified global eradication of wild poliovirus serotypes 2 and 3, and serotype 1 wild poliovirus transmission now remains only in Afghanistan and Pakistan. (Chumakov et al., 2021 ; Thompson, 2021 ; Thompson & Kalkowska, 2020 ; Thompson & Kalkowska, 2021 ; WHO, 2021b ). With these advances, immunization has been lauded as one of the biggest public health successes, saving 2–3 million lives a year without counting the contribution of COVID‐19 vaccines (United Nations Children's Fund [UNICEF], 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This section begins with a brief overview of each of the 102 studies identified by the search process summarized in Figure 1 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ,…”
Section: Resultsmentioning
confidence: 99%
“…Following the release of the 2019–2023 GPEI strategic plan [ 161 ] and post-cessation strategy [ 162 ], KRI updated its integrated model inputs to use retrospective immunization and epidemiology data through the end of 2018 and prospective inputs consistent with available information about recent programmatic performance and updated plans. The third special issue of the journal Risk Analysis on Global Poliovirus Risk Management and Modeling, published in February 2021 [ 6 ], included many of these studies, several of which appeared online in 2020. In January 2020 (prior to the COVID-19 pandemic), the KRI update of its integrated model reported the GPEI was off-track with respect to achieving its polio eradication goals [ 161 ] and attributed this primarily to the low quality of OPV SIAs [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…PV comes in three different variants and has an RNA genome and a protein capsid. Its genome is made up of positive-sense ssRNA and measures approximately 7.5 kb in length [ 125 ]. Enterovirus 71 (EV71) is also a picornavirus belonging to the genus Enterovirus and is known to cause severe neurological diseases as well as hand-foot-and-mouth disease (HFMD) in young people [ 126 , 127 ].…”
Section: Antiviral Activities Of Alkaloids Against Multiple Virusesmentioning
confidence: 99%